Role of Ultrathin Carbon Shell in Enhancing the Performance of PtZn Intermetallic Nanoparticles as an Anode Electrocatalyst for Direct Formic Acid Fuel Cells. Issue 8 (29th April 2019) - Xu, Min; Zhao, Yufei; Chen, Hong; Ni, Wei; Liu, Mingquan; Huo, Silu; Wu, Linlin; Zang, Xiaogang; Yang, Zhiyu; Yan, Yi‐Ming
Abstract: Introducing a carbon shell to Pt‐based intermetallic nanoparticles (iNPs) is an effective approach to prepare structurally ordered electrocatalysts for fuel cell applications. However, it remains a huge challenge to synthesize small‐sized Pt‐based iNPs with a concisely controlled carbon shell based on fully understanding the role of the carbon shell in the electrocatalytic performance. Herein, we report the preparation of ultrathin carbon shell (UCS)‐coated, small‐sized PtZn iNPs, which are obtained by using the simple heat treatment of polypyrrole‐coated PtZn/C (PPy−PtZn/C), which can produce a carbon shell in situ and simultaneously transfer a disordered PtZn alloy into ordered intermetallic PtZn. Interestingly, the thickness of the carbon shell can be well‐controlled by tuning the polymerization time of pyrrole (Py). The obtained PtZn iNPs (an average diameter of ca. 4 nm) coated with UCS (ca. 0.5 nm thickness) shows the best electrocatalytic performance toward the formic acid oxidation reaction. Moreover, the UCS−PtZn iNPs offers remarkable long‐term stability as an anode electrocatalyst in a constructed direct formic acid fuel cell. The results demonstrate that the UCS formed in situ only acts as a physicochemical protecting shell with high permeability for the reactants, but it does not block the catalytic reaction sites of iNPs. Abstract : In a (nut)shell : The well‐defined and small‐sized PtZn intermetallic nanoparticles coated with an ultrathin carbon shell (UCS−PtZn iNPs) are successfully prepared and used as an anode electrocatalyst for direct formic acid fuel cells. The thickness of the carbon shell can be well‐controlled by tuning the polymerization time of pyrrole. An optimized UCS−PtZn iNPs sample with an average diameter of approximately 4 nm and a carbon shell thickness of 0.5 nm exhibits best electrocatalytic performance towards for the formic acid oxidation reaction.